Comparison between indicine and taurine cattle DNA methylation reveals epigenetic variation associated to differences in morphological adaptive traits. Issue 1 (31st December 2023) - Capra, E.; Lazzari, B.; Milanesi, M.; Nogueira, G. P.; Garcia, J. f.; Utsunomiya, Y.T.; Ajmone-Marsan, P.; Stella, A.
ABSTRACT: Indicine and taurine subspecies present distinct morphological traits as a consequence of environmental adaptation and artificial selection. Although the two subspecies have been characterized and compared at genome-wide level and at specific loci, their epigenetic diversity has not yet been explored. In this work, Reduced Representation Bisulphite Sequencing (RRBS) profiling of the taurine Angus (A) and indicine Nellore (N) cattle breeds was applied to identify methylation differences between the two subspecies. Genotyping by sequencing (GBS) of the same animals was performed to detect single nucleotide polymorphisms (SNPs) at cytosines in CpG dinucleotides and remove them from the differential methylation analysis. A total of 660, 845 methylated cytosines were identified within the CpG context (CpGs) across the 10 animals sequenced (5 N and 5 A). A total of 25, 765 of these were differentially methylated (DMCs). Most DMCs clustered in CpG stretches nearby genes involved in cellular and anatomical structure morphogenesis. Also, sequences flanking DMC were enriched in SNPs compared to all other CpGs, either methylated or unmethylated in the two subspecies. Our data suggest a contribution of epigenetics to the regulation and divergence of anatomical morphogenesis in the two subspecies relevant for cattle evolution and sub-species differentiation and adaptation.